PENGARUH DIGITAL LITERASI DAN BONUS DEMOGRAFI TERHADAP TINGKAT TUNA KARYA PADA ALUMNI SMA N 1 JUNTINYUAT INDRAMAYU TAHUN 2020 - Aira Ratu Maganda Pandjaitan; Grace Orlyn Sitompul (POLITEKNIK LP3I JAKARTA, 2024)
There have been many changes that have occurred in Indonesia, one of which is changes regarding technology. These changes are also followed by a demographic bonus which is expected to occur in Indonesia from 2030 to 2040. This research aims to determine the impact of the many changes that have occurred in the current era which require Indonesia to follow suit so as not to be left behind. Some of these changes occur due to external factors such as technology which makes digital literacy a necessity as well as internal changes that are predicted to occur in 2040, namely the Demographic Bonus, namely a condition where the level of productive age becomes very high. Therefore, this research was conducted to find out the significant influence between Digital Literacy (X1) and the Impact of the Demographic Bonus (X2) on the level of unemployment among alumni of SMA N 1 JUNTINYUAT Indramayu in 2020 (Y). This research is quantitative so the media used to collect data is a questionnaire with the research population being (Alumni of SMA N 1 JUNTINYUAT Indramayu in 2020) and the sample is (Alumni of SMA N 1 JUNTINYUAT Indramayu in 2020). The questionnaire was distributed using a non-probability sampling method with purposive sampling. The results of this research show that both digital literacy and the demographic bonus have a significant influence on the level of unemployment among alumni of SMA N 1 Juntinyuat Indramayu in 2020. Keywords: Change, Digital Literacy, Demographic Bonus, Unemployment.